Renaissance medicine - Nutton, Vivian, author.
1 online resource
Keywords: "This volume offers a comprehensive historical survey of medicine in sixteenth-century Europe and examines both medical theories and practices within their intellectual and social context. Based on a wide reading of primary sources from literature and art across Europe, Renaissance Medicine is an invaluable resource for students and scholars of the history of medicine and disease in the sixteenth century"--